The content and context of hate speech : rethinking regulation and responses - Herz, Michael E.; Molna´r, Pe´ter , 1964- (Cambridge University Press, 2012)
"The contributors to this volume consider whether it is possible to establish carefully tailored hate speech policies that are cognizant of the varying traditions, histories, and values of different countries. Throughout, there is a strong comparative emphasis, with examples (and authors) drawn from around the world. All the authors explore whether or when different cultural and historical setting justify different substntive rules given that such cultural relativism can be used to justify content-based restrictions and so endanger freedom of expression"-- Provided by publisher